If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5(x + -1) = 0 Reorder the terms: 2x + 5(-1 + x) = 0 2x + (-1 * 5 + x * 5) = 0 2x + (-5 + 5x) = 0 Reorder the terms: -5 + 2x + 5x = 0 Combine like terms: 2x + 5x = 7x -5 + 7x = 0 Solving -5 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 7x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 7x = 0 + 5 7x = 0 + 5 Combine like terms: 0 + 5 = 5 7x = 5 Divide each side by '7'. x = 0.7142857143 Simplifying x = 0.7142857143
| 3(-11)[5(-3)-7(-2)]= | | 6xrqw+13xrqw=133 | | 9s-36=5s | | 64g^3-125h^3=0 | | 13(x-4)=8x-32 | | 16t^2=-h+100 | | 3/4+1/4x=3/4x-1/4 | | -4=3n-7n | | 2x-60=x | | x-2=14*2 | | 16t^2+h=100 | | 1-11-3x=32 | | x+by=c*x | | (2m-7)squared= | | 2(7)-2x=6 | | 12x-4(3x)=0 | | 4b-8b^2=0 | | x/2-1/5=x/3+1/4 | | Y+5/8=-2 | | -17x=391 | | 7y-18=-46+3y | | 6(1)-10x=77 | | 2x-5(x-2)=-6+3x-20 | | -6(8+5n)-5=6n+19 | | (8xy-y)(8xy-y)= | | 7y-10(6y-13)=77 | | 4x-24=-30+6x | | 11x+3=5x+27 | | -8=2n+2n | | 2y+7-22y= | | -7.97(-5+a)=56.586 | | 7(-6)+8y=-18 |